Application of Employability Skills and Contextual Performance Level of Employees in Government Agencies - Maripaz C. Abas (Intelektual Pustaka Media Utama, 2016)
The widespread practice of contractualization even in government institutions is a big challenge facing newly-hired employees in seeking a stable position. Researchers have argued that the quality of practice of employability skills could help employees have better job performance, provide them better working condition or status, and consequently meet the higher expectations of employers. The present study employs descriptive research design to explain the extent of application of employability skills and contextual performance. Based on The Conference Board of Canada’s Employability Skills 2000+ and Borman and Motowidlo’s Taxonomy of Contextual Performance, two sets of survey questionnaires were adopted to gather data from 220 respondents representing employers and employees from 25 government institutions. Data analysis showed that novice employees in public institutions applied their employability skills such as fundamental, personal management and teamwork skills to some extent. Moreover, results revealed that employees had satisfactory contextual performance. Thus, this may suggest that the application of employability skills and contextual behaviors should be enhanced to meet the increasing and complex challenges of their respective government agencies.